Using rhetorical structure theory in Automatic Text Summarization for Marcu-Authored Documents - Borra, Allan; Diola, Almira Mae; Ong Lopez, Joan Tiffany T.; Torralba, Phoebus Ferdiel; So, Sherwin (Philippine computing journal)
An automatic text summarizer system using Rhetorical Structure Theory (RST) is a formalism developed by Mann and Thompson (1988) that allows for discourse analysis of multi-sentence text...